Re-Sacralization of Nature and Sufi Ecotheology: Seyyed Hossein Nasr’s Contribution to Environmental Ethics in the Anthropocene - Agung Nugroho Reformis Santono; Muhammad Zainuddin; Muhammad Lytto Syahrum Arminsa; Muhammad Ikhya Ulumuddin; Tholhah; Nasirin; Aidul Fitriawan; Dannu Akbar; Nurul Jannah (Journal of Islamic Thought and Civilization, 2026)
The global ecological crisis in the Anthropocene is fundamentally a crisis of cosmology and modern spirituality, driven by an anthropocentric and secular paradigm that desacralizes nature and reduces the environment to a mere exploitable commodity. While existing Islamic ecotheology predominantly focuses on normative and legalistic frameworks, there remains a significant research gap concerning the deeper ontological and metaphysical roots of environmental degradation. This article addresses this critical gap by systematically analyzing Seyyed Hossein Nasr’s philosophical thought through a comprehensive Sufi ecotheological lens. Using a qualitative, library-based method with a Sufi-hermeneutic approach, this study examines Nasr’s major works to articulate his critique of modernity and his vision for the re-sacralization of nature. The findings reveal that Nasr’s unique contribution lies in three core pillars: (1) restoring awareness of the sacred cosmos as a tajallī; (2) reinterpreting the human role simultaneously as khalīfahand ‘abd to maintain cosmic balance; and (3) developing “sacred science” as an alternative epistemology uniting rationality with metaphysical awareness. Addressing academic critiques regarding its perceived spiritual elitism and lack of practical applicability, this study explicitly synthesizes Nasr's thought into a novel “cosmotheocentric” conceptual model. This cosmotheocentrism transcends the rigid tradition-modernity binary, offering a profound Islamic-Sufi contribution to global environmental ethics. Ultimately, it positions the re-sacralization of the cosmos not just as a theoretical ideal, but as the essential prerequisite for building a sustainable and just ecological civilization.